2018
DOI: 10.1186/s12014-018-9183-3
|View full text |Cite
|
Sign up to set email alerts
|

Urine proteomics of primary membranous nephropathy using nanoscale liquid chromatography tandem mass spectrometry analysis

Abstract: BackgroundPrimary membranous nephropathy (PMN) is an important cause of nephrotic syndrome in adults. Urine proteome may provide important clues of pathophysiological mechanisms in PMN. In the current study, we analyzed and compared the proteome of urine from patients with PMN and normal controls.MethodsWe performed two technical replicates (TMT1 and TMT2) to analyze and compare the urine proteome from patients with PMN and normal controls by tandem mass tag (TMT) technology coupled with nanoscale liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Twenty-one proteins from the 2D dataset were selected as potential protein candidates for biomarkers of the disease (Table 2). AAT, APOA4 and VIL1 concentrations have previously been shown to increase in blood plasma as CKD progresses [28][29][30][31]. Our data confirm the increased blood serum concentrations of these proteins in patients; whereas only serum AAT values correlated with elevated levels of creatinine and cytokines.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Twenty-one proteins from the 2D dataset were selected as potential protein candidates for biomarkers of the disease (Table 2). AAT, APOA4 and VIL1 concentrations have previously been shown to increase in blood plasma as CKD progresses [28][29][30][31]. Our data confirm the increased blood serum concentrations of these proteins in patients; whereas only serum AAT values correlated with elevated levels of creatinine and cytokines.…”
Section: Discussionsupporting
confidence: 85%
“…Exogenous AAT inhibited apoptosis and inflammation in renal reperfusion [28] and reduced the urine kidney injury molecule-1 (KIM-1) concentration [30]. Several studies have demonstrated increased blood plasma AAT concentrations in hypoxia [31] and acute myocardial infarction [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…With class‐specific inhibitors, serine protease activity accounted for more than 80% of the total protease activity, with the remainder being aspartate, cysteine, and metalloproteases. Using a proteomic approach, serine proteases seen in nephrotic syndrome were typically those that circulate in soluble form in the plasma and belong to the coagulation and complement cascade . Therefore, proteasuria in nephrotic syndrome reflects the translocation and excretion of active proteases from the plasma compartment into the urine.…”
Section: Proteasuria In Patients With Nephrotic Syndromementioning
confidence: 99%
“…Liquid chromatography-tandem mass spectrometry (LC-MS/MS) is a noninvasive detection method used in urine proteomics that can provide qualitative and quantitative assessments of the proteome and offer clues for biological processes in systems. LC-MS/MS has been applied in the proteomic analysis of various kidney diseases, such as membranous nephropathy [8], acute kidney injury [9], lupus nephritis [10] and IgA nephropathy (IgAN) [11]. Data-independent acquisition (DIA) by LC-MS/MS, which enables comprehensive mapping of the urinary proteome, has sufficient throughput to perform biomarker discovery studies, as all identified proteins can be precisely quantified in hundreds of samples [12].…”
Section: Introductionmentioning
confidence: 99%